DNA Barcoding Application Using CYTB (Cytochrome-B) Marks for Authentication of Patin Fish (Pangasius sp.) Products in Surabaya Area - Aulia, Wina Intan Nur; Setiawan, Edwin; Triwibowo, Radestya; Saputro, Triono Bagus; Hidayati, Dewi; Nurhayati, Awik Puji Dyah; Ridho, Muhammad Ainur Rosyid (RUMPHIUS, 2026)
DNA barcoding is a practical and accurate molecular technique for identifying processed fish products that lack morphological characteristics. However, its application is limited by the availability of reference databases, DNA quality, and primer suitability. This study aims to determine the genetic identity of pangasius catfish (Pangasius sp.) marketed in Surabaya using the Cytochrome b (CytB) gene and to evaluate PCR-RFLP as an alternative to sequencing. A total of twenty samples (fresh and frozen fillets) were analyzed through DNA extraction and PCR amplification of the CytB gene, followed by in silico and in vitro analyses.The results show that CytB demonstrates high amplification success and provides sufficient resolution for species-level identification based on Neighbor-Joining analysis with the Kimura 2-parameter model. The study confirms that the samples were genetically identified as Pangasius pangasius and Pangasius hypophthalmus. This research highlights the novelty of integrating in silico prediction with laboratory validation to improve marker evaluation in DNA barcoding studies. Furthermore, it demonstrates that CytB-based PCR-RFLP is a rapid and cost-effective alternative to sequencing for detecting species mislabeling. Overall, the CytB gene is proven to be a reliable molecular marker for species authentication, supporting traceability systems and strengthening seafood authenticity monitoring in commercial markets.